THE EFFECT OF DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY ON THE PERFORMANCE OF SHARIA COMMERCIAL BANKS IN INDONESIA (Ekspektra : Jurnal Bisnis dan Manajemen, 2022)
Islamic banks are companies whose social goals must be at least as important as their goals in making a profit. Because Islamic banks are banks that adhere to the sharia system that is guided by the Al-Quran and Al-Hadith. The level of disclosure of CSR that do Islamic banks are still low. The purpose of this study was to determine the effect of disclosure of corporate social responsibility (CSR) on the performance of Islamic Commercial Banks. This type of research is quantitative research. This type of data uses secondary data taken from the annual financial reports of Islamic Commercial Banks for the period 2012-2018. The sample is a Sharia Commercial Bank registered with Bank Indonesia and the financial service authorities, amounting to 13 banks. The dependent variable is financial performance as proxied by ROA and ROE, while the independent variable is CSR which is measured by the social disclosure index. Data collection techniques using documentation techniques. The data analysis technique used multiple linear regression. The results showed that disclosure of corporate social responsibility (CSR) has a positive effect on return on assets and return on equity.